The Effect Of Hexagon Fraud Dimensions And Abuse Of Information Technology On Academic Fraud (Case Study On Feb Students Of Trisakti University) - Zayyan Nailah; Murtanto Murtanto (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine how academic fraud is impacted by hexagon fraud (Pressure, Opportunity, Rationalization, Capability, Arrogance, and Collusion) dan misuse of information technology. 103 accounting students from Trisakti University made up the sample for this study. In this study, questionnaires were given out to collect the data. This study employed multiple linear regression analysis as its analysis method. The investigation's findings, which are the exclusive conclusions of this study, are as follows: (1) pressure has no bearing academic cheating (2) opportunity has no bearing on academic cheating (3) rationalization has no bearing on academic cheating (4) Academic cheating is not considerably impacted by capability (5) Academic cheating is considerably impacted by arrogance (6) Academic cheating is considerably impacted by collusion (7) Academic cheating is not significantly impacted by misuse of information technology.